2013
DOI: 10.1016/j.talanta.2013.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic voltammetry: A tool to quantify 2,4,6-trichloroanisole in aqueous samples from cork planks boiling industrial process

Abstract: Chloroanisoles, namely 2,4,6-trichloroanisole, are pointed out as the primary responsible of the 27 development of musty off-flavours in bottled wine, due to their migration from cork stoppers, which 28 results in huge economical losses for wine industry. A prevention step is the detection of these 29 compounds in cork planks before stoppers are produced. Mass spectrometry gas chromatography is 30 the reference method used although it is far beyond economical possibilities of the majority of cork 31 stoppers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Other techniques for the extraction of aldehydes and other VOCs have been used in cork- and wood-based samples, such as solid-phase microextraction, dynamic headspace, , and simultaneous distillation and extraction . Although the most common analytical techniques used are spectrophotometry, , liquid chromatography, , and gas chromatography, ,,, other techniques such as cyclic voltammetry have successfully been used for the analysis of VOCs in cork- and wood-based samples.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques for the extraction of aldehydes and other VOCs have been used in cork- and wood-based samples, such as solid-phase microextraction, dynamic headspace, , and simultaneous distillation and extraction . Although the most common analytical techniques used are spectrophotometry, , liquid chromatography, , and gas chromatography, ,,, other techniques such as cyclic voltammetry have successfully been used for the analysis of VOCs in cork- and wood-based samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of this proof-of-concept study, an LOD of 200 µg L −1 of TCA and good discrimination against the interferant TCP were achieved. Finally, Peres et al [78,79] reported the use of cyclic voltammetry (CV) for determination of TCA in aqueous cork extracts, resulting from the immersion of cork planks in boiling water (60 min), which is a standard component of commercial cork processing. Tetrabutylammonium perchlorate (TBAP, 0.1 M) was used as the supporting electrolyte in order to increase current intensity.…”
Section: Biosensors For the Detection Of Haloanisoles In Wine And Bevmentioning
confidence: 99%
“…The aqueous samples provided were used after being diluted with either MeOH or ACN containing 0.17 M TBAP, in order to obtain a volumetric proportion of 1:1 or 3:2 and a final solution with 0.1 M TBAP. The 2,4,6-TCA concentrations, before and after standard solution addition were calculated by using a similar procedure as that described in the previous section for ACN/water solutions, but taking into account the standard addition calibration method with volume correction, due to the dilution factor [20]. Thus, a linear relationship was established between the total current amplitude multiplied by the final volume after each addition of the standard solution and the total added volume of the standard 2,4,6-TCA in ACN/water with 0.1 M of TBAP.…”
Section: Sample Preparationmentioning
confidence: 99%